Why Do We Use Instagram? Motives of Active and Passive Instagram Users - Agitia Kurniati Asrila; Rizal Kurniawan (Jurnal Neo Konseling, 2023)
The popularity of social media has not faded yet. One of the latest popular social media is instagram. Based on the differences in features and patterns of interaction, this research is conducted to find out motives of instagram users. This research uses a qualitative approach, therefore the researcher is the main instrument. Using an open-ended questionnaire, this study was conducted on 136 early adults who are instagram users. After conducting a thematic analysis, the results of the study stated that there are several motives underlie individuals using instagram. Furthermore, active and passive users known as the type of the instagram users. The conclusion from this study is both users perform repetitive behaviors when using instagram, with different motives and patterns.